EVALUATION OF THE BERSINAR PROGRAM AS AN EFFORTS TO PREVENT ILLEGAL DRUG CIRCULATION - M. Mas'ud Said; Dwi Afriska; Hayat Hayat (Journal of Social and Economics Research, 2025)
The circulation of illicit drugs in correctional institutions remains a serious problem that undermines the objectives of inmate rehabilitation. To address this issue, Malang Class I Correctional Institution implemented the Drug-Free Program (BERSINAR) as an effort to prevent and control drug distribution within the prison environment. This study aims to evaluate the implementation and effectiveness of the BERSINAR Program in preventing illicit drug circulation. The research employed a descriptive qualitative approach, with data collected through interviews, observations, and documentation. Program evaluation was analyzed using public policy indicators proposed by William N. Dunn, namely effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. The findings indicate that the BERSINAR Program has generated positive impacts through routine urine tests, cell inspections, counseling activities, religious guidance, and rehabilitation programs. However, the goal of achieving a drug-free prison has not been fully realized due to ongoing drug smuggling practices, manipulation of urine tests, and limited supervision. In addition, constraints in human resources, facilities, and access to rehabilitation services have hindered the program’s optimal and equitable implementation. This study highlights the importance of strengthening supervision, resources, and target accuracy to enhance the effectiveness and sustainability of the BERSINAR Program.